Lymphatic drainage efficiency: a new parameter of lymphatic function. (September 2018) - Keramida, Georgia; Wroe, Emma; Winterman, Nicola; Aplin, Mark; Peters, A Michael
Background: Following convection from blood capillaries, plasma proteins are transported to loco-regional lymph nodes in two stages: first, uptake into peripheral lymphatics, and second, transport to nodes. Purpose: To introduce a new parameter of lymphatic function that quantifies stage 2 – lymphatic drainage efficiency (LDE). Material and Methods: Percentage injected activity (IIQ) in ilio-inguinal nodes 150 min following subcutaneous foot web-space injection of Tc-99 m-nanocolloid was measured in 102 patients undergoing lymphoscintigraphy using a method in which a standard is placed by image guidance over the nodes. Percentage activity leaving the injection depot by 150 min ( k ) was measured in 60/102 patients. LDE (%) = 100 × (IIQ/ k ). Abnormal lymphoscintigraphy was defined qualitatively as: (i) no activity in ilio-inguinal nodes at 45 min or negligible activity at 150 min (delay); (ii) lymph diversion through skin and/or deep system; and (iii) focal tracer accumulation suggesting cellulitis. Results: Scintigraphy was bilaterally normal in 82 limbs, unilaterally normal in 40 limbs and abnormal in 82 limbs. IIQ correlated with k in bilaterally normal (r = 0.86; n = 52), unilaterally normal (r = 0.67; n = 27), and abnormal (r = 0.82; n = 41) limbs. IIQ, k, and LDE were significantly lower in unilaterally normal (9.3 ± 5.4%, 13.8 ± 7.1%, and 65 ± 30%) compared with bilaterally normal limbs (15.4 ± 8.4% [ P  > 0.0001], 18.3 ± 8.9% [ P  = 0.025], and 84 ± 30% [ P  = 0.01]). LDE was lower in limbs displaying skin diversion and/or delay. Conclusion: LDE is a new quantitative index that has potential value in clinical research but requires further clinical evaluation. Abnormal quantitative indices indicate that limbs unilaterally normal on lymphoscintigraphy are not functionally normal.